MORE EDUCATION PROGRAM AND NEW MODEL OF FULLTIME SCHOOL IN SÃO PAULO: SIMILARITIES AND SINGULARITIES - Elisangela Maria Pereira Schimonek; Teise de Oliveira Guaranha Garcia (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
The paper presents and discusses the Programs More Education and the New Model of Fulltime Education of São Paulo state. The first was established by the MEC in 2008- through agreements with states and municipalities- and the second, by the Secretary of education of São Paulo state in 2012. Both extended the students school day, adopting different models, but converging at some points. The study analyzes the programs considering: the stated objectives, the target audience, the concept of integral education, the presence of the private sector, the selection of schools, professionals involved and sources of funds. We used as a methodology to analyze regulations and official documents, as well as consultations with secondary sources. To obtain the data, we used primary sources - regulations and official documents, and secondary sources, analyzing the content of the documents. In addition, an interview with a public manager was also used. It should be noted that the State Program establishes the differentiation between professionals of the same network, meets a very small number of students with conditions infrastructural qualitatively superior compared to regular schools. The More Education Program covers the priority schools, and promotes "selection" of students from the criterion degree of social vulnerability. Keywords: Integral Education. More Education. New Model of Fulltime Education - SP.